UPAYA PENGAWASAN IMIGRASI TERHADAP PENYALAHGUNAAN VISA IZIN TINGGAL WNA DI KABUPATEN BULELENG - Ni Luh Putu Trisna Yuliartini; Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Universitas Pendidikan Ganesha, 2023)
This study aims to find out and analyze immigration control efforts against the misuse of stay permit visas by foreign nationals in Buleleng Regency, as well as find out and analyze how immigration controls over abuse of stay permit visas by foreign nationals, as well as find out and analyze how the forms of supervision by the immigration authorities in the misuse of a residence permit visa. In this study, the type of research used is empirical legal research using descriptive research characteristics. The data and data sources used in this study are primary data and secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques used in this research are document study techniques, observation techniques, and interview techniques. The sampling technique used was a non-probability sampling technique to determine the subject using a purposive sampling technique. Furthermore, the data obtained was processed and analyzed qualitatively. The results of the study indicate that the form of supervision by the immigration authorities in preventing the misuse of visas for residence permits for foreign nationals in Buleleng Regency includes immigration control efforts in conducting immigration socialization in the form of visits to village officials, then implementing foreigner reporting applications (APOA), and immigration administrative action. Immigration authorities carry out administrative supervision and field supervision. Then the immigration authorities faced several obstacles in carrying out supervision related to the misuse of visas for residence permits for foreign citizens in Buleleng Regency, namely the ease of granting visa-free permits to foreign nationals, then due to human resource factors, then due to language differences, and the lastly because of the community factor which is an obstacle in supervising the misuse of visas with residence permits in Buleleng Regency.